2021
DOI: 10.18016/ksutarimdoga.vi.804177
|View full text |Cite
|
Sign up to set email alerts
|

Determination of The Antimicrobial, Antioxidant and Cytotoxic Activity of Paulownia tomentosa Steud.

Abstract: Paulownia tomentosa, used in traditional Chinese medicine, is used in the treatment of diseases such as bronchitis and asthma thanks to its biological activities. In addition, it is known to have antimicrobial, antioxidant, anticancer effects and it is also used in the treatment of diseases such as dysentery, gonorrhea, hemorrhoids. In this study, the antimicrobial activity of extracts obtained from methanol solvent of flower and petal parts of P. tomentosa was determined according to the disk diffusion method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The antimicrobial, antioxidant and cytotoxic effects of extracts of the flowers, petals, bark, leaves and wood parts of P. tomentosa were investigated. The results showed that the best antimicrobial activity was achieved by the extract of the flower part of P. tomentosa against S. aureus 23 . In studies on the leaves and flowers of P. tomentosa , antioxidant properties were analysed, and catechin was found to have the highest phenolic content.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial, antioxidant and cytotoxic effects of extracts of the flowers, petals, bark, leaves and wood parts of P. tomentosa were investigated. The results showed that the best antimicrobial activity was achieved by the extract of the flower part of P. tomentosa against S. aureus 23 . In studies on the leaves and flowers of P. tomentosa , antioxidant properties were analysed, and catechin was found to have the highest phenolic content.…”
Section: Introductionmentioning
confidence: 99%